Association between circulating adipokines, radiographic changes, and knee cartilage volume in patients with knee osteoarthritis. (3rd May 2016) - Zheng, S; Xu, J; Xu, S; Zhang, M; Huang, S; He, F; Yang, X; Xiao, H; Zhang, H; Ding, C
Abstract : Objectives : To explore the associations between serum adipokine levels, radiographic osteoarthritis (ROA) severity, and articular cartilage volume in patients with knee OA. Method : A cross-sectional sample of 205 patients (aged 45–74 years) with knee OA were consecutively recruited to the Anhui Osteoarthritis (AHOA) study. ROA was assessed using the Kellgren–Lawrence (KL) grading system (grades 0–4). Knee cartilage volume was determined using fat-saturated T1-weighted magnetic resonance imaging (MRI). Serum levels of the adipokines leptin, adiponectin, and resistin were measured by using an enzyme-linked immunosorbent assay (ELISA). Results : Serum adiponectin, but not serum leptin or resitin, was significantly associated with reduced ROA severity in univariable analyses and this association remained significant after adjustment for age, sex, body masss index (BMI), and disease duration [β = −0.012, 95% confidence interval (CI) −0.021 to −0.002]. In ROA patients, leptin was significantly and positively associated with knee cartilage volume at patellar and medial tibial sites in both unadjusted and adjusted analyses (β = 0.006, 95% CI 0.02–0.010 for medial tibia and β = 0.009, 95% CI 0.001–0.018 for patella sites) but adiponectin and resistin had no significant associations with cartilage volume. In non-ROA patients, leptin, adiponectin, and resistin were not significantly associated with cartilage volume at any site. Conclusions : Serum levels of leptin are independently associated with increased knee cartilage volume. In addition, serum adiponectin is significantly and negatively associated with ROA severity, suggesting a potentially protective effect.